Evaluation of the effectiveness of treatment with prednisone and azathioprine of autoimmune hepatitis in children - Pniewska, Anna (Prz Gastroenterol, 2015)
INTRODUCTION: Autoimmune hepatitis is rarely diagnosed in children, but the course of the disease is often aggresive. Combination therapy with prednisone and azathioprine improves the prognosis of patients. AIM: To evaluate the effectiveness of combination therapy with prednisone and azathioprine of autoimmune hepatitis (AIH) in children. MATERIAL AND METHODS: There was a retrospective analysis of the medical records of 15 patients with AIH, diagnosed before18 years of age, treated in the Provincial Infectious Diseases Hospital in Bydgoszcz in the years 2002 to 2013. We analysed the results of laboratory tests, ultrasound examination, endoscopy, and morphological liver pictures, as well as periods of exacerbation of inflammation and side effects of therapy. RESULTS: Biochemical remission of the disease was achieved on average after 36 days of treatment. Histopathological regression in the control liver biopsy was found in 7/15 patients and progression in 2/15 patients. In the study group 10/15 patients experienced exacerbation of the disease from 1 to 3 times during observation, with an increase of ALT activity to greater than 3 norm, and the remaining 5/15 patients had no increase of ALT activity. In total, 10 patients in the study group experienced 17 exacerbations. In 13/17 cases of exacerbations they were associated with a reduction in the dose of immunosuppressive drugs. There was no correlation between the biochemical exacerbation and changes in the histopathological image. Steroidside effects occurred in 14/15 patients. CONCLUSIONS: The treatment allows for biochemical remission of the disease and significantly improves the prognosis of most patients. However, significant side effects of treatment indicate the need for further exploration of effective and safe therapy, especially in the paediatric population.